Muhammad Al-Ghazali's Approach in his Interpretation Towards an Objective Interpretation of the Surahs of the Noble Qur'an - Deek, Muhammad Youssef Al (Universitas Muhammadiyah Surakarta, 2025)
Research Objectives: The research aims to demonstrate Muhammad al-Ghazali's approach to the objective interpretation of the surahs of the Holy Quran, and the extent to which it meets the conditions for the objective interpretation of the surah. Study Methodology: The research followed an inductive and descriptive approach, studying the entire interpretation. In light of this study, the issues related to the method of the objective interpretation of the surah were identified, and the main and subheadings were developed from there. Results: The most important results reached by the research are that al-Ghazali's approach represents concise spiritual reflections and insights, focuses on cognitive foundations, and generally fulfills the conditions for the objective interpretation of the surahs of the Quran, with the exception of some conditions. Research Originality: The value of the research is demonstrated by the extent to which the conditions for the objective interpretation of this book are met.